NURTURING CUSTOMERS LOYALTY ON ISLAMIC BANK: THE ROLE OF SATISFACTION AND TRUST AS MEDIATION - Sulis Riptiono; Muhammad Baehaqi (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2024)
Introduction: Customer loyalty is a fundamental point in relational marketing that must be maintained and maintained by service providers. The urgency of nurturing loyalty of customers is the goal of this research, namely by developing a framework of customer loyalty in shariah banks using the antecedents to be tested. Method: A total of 250 Indonesian Islamic bank customers in Central Java were used as respondents taken using a convenience sampling technique. The collected data were tested, and the data were analysed using SEM with the AMOS statistical software. Result: The finding of the study shows from the nine hypotheses, there are six hypotheses accepted and three hypotheses rejected. High intrinsic religiosity of customers will increase customer satisfaction, trust and loyalty. Meanwhile, extrinsic religiosity is only able to make customers believe in Islamic banks, but is unable to influence satisfaction and loyalty. Other findings show that customer loyalty is based on their trust in Islamic bank services but is not directly influenced by satisfaction. Conclusion and Suggestion: Meanwhile, customer trust in Islamic banks is formed because of their satisfaction with the service. Although satisfaction is not significant on loyalty, its impact can affect trust, and trust is the key to increasing loyalty. This study's findings offer a new perspective on Islamic bank marketing strategies. By promoting proper service, product development, and operational excellence, these strategies can help build customer trust.